Non-conventional machining of Monel-400 alloy: a critical review of techniques, challenges, and sustainable prospects - Singh, Kamalpreet; Kumar, Raman; Singh, Sehijpal; Kumar, Rajender; Sead, Fadhil Faez; Lozanović, Jasmina (Frontiers in Mechanical Engineering, 2025)
Monel-400, a nickel-copper-based alloy, is renowned for its exceptional corrosion resistance, high strength, and toughness across diverse operating environments. However, these desirable properties also make Monel-400 a challenging material to machine using conventional techniques, leading to excessive tool wear, poor surface finish, and high thermal stresses. There is currently no comprehensive review that systematically consolidates and compares non-conventional machining approaches applied to Monel-400 alloy. This review critically examines the non-conventional machining methods employed to address these challenges, including Electric Discharge Machining (EDM), Wire EDM (WEDM), Electrochemical Machining (ECM), Plasma Arc Cutting (PAC), Abrasive Water Jet Machining (AWJM), Photochemical Machining (PCM), and Hot Machining. A systematic comparison of process performance, surface integrity, material removal rate (MRR), Tool Wear Rate (TWR), Surface Roughness (Ra), and optimization strategies is presented. Key advancements such as hybrid dielectrics, cryogenic treatments, near-dry machining, and AI-based optimization techniques are discussed. Challenges related to surface defects, environmental sustainability, tool degradation, and process scalability are highlighted, along with identified research gaps. Future research directions emphasize the development of eco-friendly machining solutions, hybrid machining systems, real-time adaptive control, and life cycle assessments to enable sustainable industrial applications. This review consolidates fragmented knowledge, provides a roadmap for future innovation, and supports the advancement of efficient, precise, and environmentally responsible machining practices for Monel-400.